The Mediating Role of Employee Commitment: The Influence of Organizational Citizenship Behavior (OCB) on Employee Performance - M Amri Alkaromi; Yoyok Subagiono; Bandot Bisowarno; Yayah Ikhda Nevia; Nurul Qomariah (www.amertainstitute.com, 2024)
Every organization must improve its performance, whether it is a government or private organization. Improving performance is important in an effort to achieve previously designed goals in an organization. This study aims to determine the effect of organizational citizenship behavior (OCB) on employee performance with commitment as an intervening variable on employees of the Jember Regency Health Office. This study is a type of comparative causal research. The data used in this study are primary data. The population in this study were employees at the Jember Regency Health Office who have the status of State Civil Apparatus (ASN and PPPK) including employees of the Health Center and UPTD as many as 1,531 people. The sample was determined by the Slovin formula as many as 100 respondents. Descriptive analysis and inductive analysis were carried out to achieve the stated goals. The results of the study stated that organizational citizenship behavior (OCB) had a positive and significant effect on employee commitment and employee performance. Employee commitment had a positive and significant effect on employee performance. Organizational citizenship behavior (OCB) had a positive but not significant effect on employee performance through employee commitment.